Paul Solman videos to accompany McConnell and Brue economics, macroeconomics and microeconomics 16th edition - Nelson, Gerald C. (New York : McGraw-Hill, 2005)
Contains Paul Solman videos on DVD that accompany McConnell and Brue books, economics, macroeconomics and microeconomics 16th edition. This videos is for chapter 1-4, 6, 8, 12, 13, 15 for that book.
For use with DiscoverEcon go to www.mcconnell16.com/discoverecon. Code to access online DiscoverEcon : gwasz-mghkp-fvazv.
Keywords: Economics; Microeconomics; Macroeconomics